Pesticides and health risks for banana workers in Vale do Ribeira, Brazil (Research, Society and Development, 2022)
The objective was to investigate and understand the health risks related to pesticide exposure from the perceptions of banana workers, in a region of Vale do Ribeira-SP. The study had two stages. In the first stage, a survey of banana workers linked to the territory of a Family Health Strategy team in Vale do Ribeira-SP was carried out, and a questionnaire was applied to obtain demographic and work-related data. In the second stage, selection of subjects to carry out individual semi-structured interviews for thematic content analysis. Thirty-six subjects participated in the study, most of them male (94.4%), with schooling up to elementary school (63.9%). Regarding pesticides, the most used by workers were: paraquat (61.9%), glyphosate (47.6%) and carbofuran (28.6%), with more than one pesticide in use. Of the workers, 61.1% reported the presence of health problems related to exposure to pesticides. The interviews were carried out with 11 male workers, aged between 28 and 46 years, and with incomplete elementary education. In the interviews, several situations of exposure to pesticides, health symptoms related to pesticides, inadequate supply and use of protective equipment, among others, emerged. The use of pesticides in banana farming in the region of this study is exposing workers to health and safety risks at work, requiring greater attention and inspections, in addition to more effective Public Policies.